Evaluation of microbial load in cut fruits sold by vendors in Kota Bharu - Sabri, Nurul Aqillah Ahmad (Universiti Sains Malaysia, 2016)
Fresh cut products such as fruits are highly demand by consumer nowadays. Fresh cut fruits promote good health but harbor a wide range of microbial contaminants. Slicing of the fruits may cause tissue disruption, which lead to high respiration rate. Higher respiration rates in fruits may cause metabolism to active, then cause fruits to deteriorate. Outbreaks have been linked with cut watermelon, papaya, pineapple, honeydew and guava. Factor influencing microbial load in cut fruits such as unclean seller and equipment, pH of fruits, sugar content, surface area and plating method. To evaluate the microbial load of cut fruits in Kota Bharu, 10 samples of different fruits were purchased from two vendors. Pour plate and spread plate method have been used to culture microbial load. For pour plate method, microbial load ranged from 5.08 x 102 to 9.00 x IO4 cfu/ml in cut fruit sold by cafeteria vendor and from 3.36 x 102 to 2.80 x 103 cfu /ml in cut fruits sold by roadside vendor. As for spread plate method, microbial load varied from 1.27 x 104 to 3.24 x 106 cfu /ml in cut fruit sold by cafeteria vendor and 7.60 x 103 - 8.10 x 106 cfu /ml in cut fruit sold by roadside vendor.